Pengaruh Suasana Café, Kualitas Pelayanan Dan Keanekaragaman Produk Terhadap Loyalitas Konsumen Di Om Ayam Sambal Ijo - Imam Bukhori; Agus Widarko; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract Based on research conducted with the aim of analyzing the effect of Café Atmosphere, Service Quality, Product Diversity on Consumer Loyalty at Om Ayam Sambal Ijo. The sample in this study were 88 customers of Om Ayam Sambal Ijo. The sampling technique used is purposive sampling where every customer who has made a repeat purchase has the opportunity to be a sample. The analytical method used in this research is multiple linear regression analysis with hypothesis testing using F test and t test. From this study, it was found that partially and simultaneously the variables of cafe atmosphere, service quality, product diversity had an effect to consumer loyalty. Keywords: Café Atmosphere, Service Quality, Product Diversity, Consumer Loyalty